What values motivate farmers to adopt climate-smart practices? Empirical evidence from a means-end chain analysis in Kenya - Ngigi, Marther (International Food Policy Research Institute, 2014)
This brief presents the main insights from a study that assessed how the values and motivations of Kenyan farmers influence their adaptation of climate-smart practices in crop and livestock management.